Microstructure characteristics of FeMo–Sialon ceramic composite - Yang, Jing-Zhou; Huang, Zhao-Hui; Hu, Xiao-Zhi; Fang, Ming-Hao; Liu, Yan-Gai; Huang, Jun-Tong (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2011)
A new metal–Sialon based ceramic composite of FeMo–Sialon has been processed using Si 3N 4, α-Al 2O 3 and FeMo70 alloy powders as the main raw materials. To explain why this composite has excellent mechanical properties, microstructure characterizations are carried out using the transmission electron microscopy (TEM) and selected area electron diffraction (SAED). The results show that FeMo, FeSi 2 and Mo have formed an alloy mixture of Mo–Fe–Si in the FeMo–Sialon ceramic composite. Elongated β-Sialon crystals, interlacing with each other, vary in size. The Y-SiAlON glass, as an inter-granular phase, surrounds the grain boundaries of β-Sialon crystals. Some of β-Sialon crystals are semi-surrounded by dumbbell-like Mo–Fe–Si particles. The good mechanical properties of FeMo–Sialon composite are greatly dependent on the elongated Sialon grains and Mo–Fe–Si particles with interlocking structures.